Serum uric acid as a prognostic indicator in acute ischemic stroke - Kaspa, Chandana; Govindu, Shankar (International Journal of Research in Medical Sciences, 2020)
Background: Association between serum uric acid (SUA) and the outcome of acute ischemic stroke is debated and needs to be evaluated. The present study was conducted to study the serum uric acid concentration as an indicator of outcome among acute ischaemic stroke and to determine the role of serum uric acid as a risk factor for acute ischemic stroke. Methods: An observational study where 50 patients who presented within 48 hours of onset of stroke admitted to medical wards of government general Hospital Guntur were selected for the study. Results: Out of 50 patients included for the study, 6 belonged to the age group of 30-40 years. Majority were male (66%) and 44.5% of the males and 76.5% of females showed raised serum uric acid levels. 25 out of 50 patients were diabetic (i.e. 50%) Among them 16 had serum uric acid >6 mg% (ie.64%), 56% of the patients were hypertensive and among them 71% were found to have uric acid levels greater than 6mgs%, 38 out of 50 patients had bad outcome, with elevated uric acid levels found 30 among them. In the present study, BMI and outcome of Stroke were significantly associated with Serum Uric acid levels. Conclusions: Serum uric acid levels can be used as a prognostic indicator as a marker for increased risk of stroke. Elevated serum urate concentration may stratify risk of death after acute stroke.